Method for detecting residual alkali on surface of sodium ion battery positive electrode material
By using the carbon-sulfur method to detect residual alkali content in the positive electrode material of sodium ion battery under the action of acidic additives and fluxes, the problems of low accuracy and complex operation of the existing titration method are solved, and the detection effect of high accuracy and simple operation is achieved.
Patent Information
- Application Number
- CN202411674492.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-24
- Publication Date
- 2025-02-28
AI Technical Summary
The titration method for detecting residual alkalis of sodium ion battery positive electrode materials in the prior art has problems such as low accuracy, poor repeatability and complex operation. Especially in aqueous solution, the positive electrode materials of sodium ion battery tend to undergo proton exchange reaction with water, resulting in the inability to accurately determine the residual alkali content.
The residual alkali content in the positive electrode material of the sodium ion battery is detected by the carbon-sulfur method using suitable acid additives and fluxes. The specific steps include measuring the carbon content of the sample to be tested under the action of the acid additives and fluxes, and then calculating the residual alkali content.
It improves the accuracy and repeatability of the detection, is easy to operate, and can accurately measure the residual alkali content on the surface of the positive electrode material of sodium ion battery, solving the shortcomings of traditional titration methods.
Smart Images

Figure BDA0005146692200000031 
Figure BDA0005146692200000051 
Figure BDA0005146692200000052
Abstract
Description
[0001] This application is a divisional application of the invention patent with application number 202410993604.4, application date July 24, 2024, and patent name “A method for detecting residual alkali on the surface of sodium ion battery positive electrode material”. Technical Field
[0002] The invention belongs to the technical field of sodium ion batteries and the field of analysis and testing, and specifically relates to a method for detecting residual alkali on the surface of a positive electrode material of a sodium ion battery. Background Art
[0003] As a new energy storage technology, sodium-ion batteries have attracted widespread attention due to their unique advantages, such as abundant resources, low cost, safety and reliability. As an important component of sodium-ion batteries, the performance of cathode materials directly affects the overall performance of the battery. The residual alkali problem, as an important characteristic of sodium cathode materials, has a profound impact on the long-term stability and safety of the battery.
[0004] Residual alkali refers to the alkaline compounds formed by alkali metal ions, hydroxide and carbonate that have not reacted completely during the preparation of positive electrode materials. The presence of residual alkali may lead to a series of problems. First, excessive residual alkali will cause the positive electrode material to have a jelly-like slurry during the electrode processing. Second, residual alkali may cause bloating during the battery cycle, affecting safety.
[0005] At present, the general method for testing residual alkali in the industry is to improve on the traditional residual alkali titration test method of lithium batteries. Ethanol is used to dissolve the residual alkali (sodium hydroxide) of the positive electrode material, and ethylene glycol is used to dissolve the residual alkali (sodium carbonate) of the positive electrode material, and then titrate and test them separately to obtain their contents.
[0006] The improved titration test method used in the patent publication CN113092458 A is to test the residual alkali (sodium hydroxide) of the positive electrode material by using an ethanol solution, but the titration of the residual alkali (sodium carbonate) is only tested by using an aqueous solution. The positive electrode material will quickly undergo a proton exchange reaction with water molecules in the aqueous solution to generate a large amount of sodium hydroxide, which affects the titration result and makes it impossible to accurately obtain the residual alkali (sodium carbonate) value.
[0007] The test of residual alkali (sodium carbonate) of positive electrode materials in the patent publication CN 116858989 A also uses an improved titration test method for testing: the residual alkali (sodium carbonate) of the positive electrode material is dissolved and filtered out by ethylene glycol solution and a titration test is performed. Although this method can avoid the proton exchange reaction of the positive electrode material, the ethylene glycol solution is filtered slowly due to viscosity problems during the dissolution process of the residual alkali (sodium carbonate) of the positive electrode material of the sodium ion battery, and the positive electrode material filtrate cannot be completely filtered to obtain the positive electrode material filtrate; at the same time, the color of the ethylene glycol filtrate is orange-yellow, and the color will still be light yellow even after dilution with an aqueous solution. This color conflicts with the color change of the indicator during acid-base titration, making it difficult to judge the titration end point, affecting the titration result, and unable to accurately obtain the residual alkali (sodium carbonate) content.
[0008] Therefore, in the prior art, there are a series of problems in the traditional titration method for measuring positive electrode materials of sodium ion batteries. First, due to poor stability in water, positive electrode materials of sodium ion batteries are very likely to undergo proton exchange reactions with water to generate a large amount of sodium hydroxide, which makes it impossible to test residual alkali by the traditional titration method; second, although the use of ethylene glycol or ethanol as a solvent for titration solves the problem of sodium dissolution, the accuracy of this method is low, the repeatability is poor, and the test operation is complicated. Summary of the invention
[0009] The purpose of the present invention is to provide a method for detecting residual alkali on the surface of positive electrode materials of sodium ion batteries in view of the problems existing in the prior art. Compared with the traditional titration method, the method is simple in operation, has high data reliability and good repeatability.
[0010] The residual alkali in the positive electrode material of the sodium ion battery is mainly sodium carbonate and sodium hydroxide. The residual alkali content is usually detected, that is, the content of sodium carbonate is detected. The present invention uses a suitable acidic additive and flux, and the content of sodium carbonate can be accurately measured by the carbon-sulfur method.
[0011] The purpose of the present invention can be achieved by the following scheme:
[0012] The present invention provides a method for detecting residual alkali on the surface of a positive electrode material of a sodium ion battery, comprising the following steps:
[0013] The sample to be tested is subjected to the action of an acidic additive and a flux, and the carbon content in the sample to be tested is measured by a carbon-sulfur method, and then the residual alkali content in the sample to be tested is calculated;
[0014] The flux comprises a first flux and a second flux; the first flux is metal tungsten, and the second flux is one or more of iron, copper, and tin.
[0015] As an embodiment of the present invention, the sample to be tested is a sodium ion battery positive electrode material powder. The sodium ion battery positive electrode material can be a layered oxide positive electrode material, such as sodium nickel iron manganate, sodium nickel manganate, sodium copper iron manganate, etc.
[0016] As an embodiment of the present invention, the residual alkali refers to at least one of the alkaline compounds formed by alkali metal ions and hydroxide or carbonate. Preferably, the residual alkali includes an alkaline compound formed by an alkali metal ion and carbonate or carbonate and hydroxide. More preferably, the residual alkali includes sodium carbonate, or sodium carbonate and sodium hydroxide.
[0017] As an embodiment of the present invention, the mass ratio of the sample to be tested to the acidic additive and the flux is 0.05-0.3:0.02-0.5:1.6-2.3. The mass fraction of the sample to be tested can range from 0.05 to 0.08, 0.08 to 0.1, 0.1 to 0.15, 0.15 to 0.2, 0.2 to 0.25, and 0.25 to 0.3; the mass fraction of the acidic additive can range from 0.02 to 0.05, 0.05 to 0.1, 0.1 to 0.15, 0.15 to 0.2, 0.2 to 0.25, 0.25 to 0.3, 0.3 to 0.35, 0.35 to 0.4, 0.4 to 0.45, and 0.45 to 0.5; the mass fraction of the flux can range from 1.6 to 1.7, 1.7 to 1.8, 1.8 to 1.9, 1.9 to 2.0, 2.0 to 2.1, 2.1 to 2.2, and 2.2 to 2.3.
[0018] As an embodiment of the present invention, the mass fraction ratio of the first flux and the second flux is 1.5-1.8:0.1-0.5. The mass fraction of the first flux can range from 1.5-1.6, 1.6-1.7, 1.7-1.8; the mass fraction of the second flux can range from 0.1-0.2, 0.2-0.3, 0.3-0.4, 0.4-0.5. The first flux (metal tungsten) is a conventionally added solvent used in sulfur-carbon monitoring, but in the residual alkali test of the sodium ion battery positive electrode material of the present invention, only the first flux is used, and some residual alkali will still remain after the sample to be tested is burned, resulting in inaccurate test results. The present invention is a compound combination of two fluxes in a specific ratio, which can improve the degree of combustion of residual alkali in the sample to be tested, greatly reduce the residual amount of residual alkali, and improve the release rate of C and S and the test accuracy.
[0019] As one embodiment of the present invention, the acidic additive is B2O3 powder.
[0020] As an embodiment of the present invention, the instrument used in the sulfur-carbon method is an infrared carbon-sulfur analyzer, which measures the CO2 concentration in the combustion gas by infrared absorption method, and calculates the carbon content in the sample to be tested. Specifically, during the test, the second flux and the acidic additive can be weighed into a crucible, the sample to be tested is added to the crucible, and then the first flux is added. The weighing mass parameters of the sample to be tested, the flux, etc. are input into the instrument software, and then the crucible is placed at the instrument injection end to start the test. After the test is completed, the carbon content in the sample to be tested is recorded.
[0021] As an embodiment of the present invention, the content of residual alkali is calculated as follows:
[0022] The carbon content in the sample to be tested is x1, and the total residual alkali (sodium carbonate) content of the sample to be tested is calculated according to the following formula:
[0023]
[0024] Among them, M C is the molar mass of carbon, is the molar mass of sodium carbonate.
[0025] As an embodiment of the present invention, the sample to be tested is also pretreated before detection, and the steps are as follows: the sample to be tested is sintered in a CO2 atmosphere to obtain a pretreated sample to be tested. After pretreatment, the residual alkali measured includes sodium carbonate and sodium hydroxide. Although the detection of residual alkali is usually mainly for sodium carbonate, the difference in the positive electrode material of the sodium ion battery and its preparation process leads to differences in the composition and content of the residual alkali. The content of sodium hydroxide in some positive electrode materials is not lower than that of sodium carbonate. Therefore, it is necessary to pretreat the positive electrode material to improve the detection accuracy of the total residual alkali.
[0026] As an embodiment of the present invention, the mass ratio of the pretreated sample to be tested to the acidic additive and flux is 0.05-0.3:0.02-0.5:1.6-2.3. The mass fraction of the sample to be tested can range from 0.05 to 0.08, 0.08 to 0.1, 0.1 to 0.15, 0.15 to 0.2, 0.2 to 0.25, and 0.25 to 0.3; the mass fraction of the acidic additive can range from 0.02 to 0.05, 0.05 to 0.1, 0.1 to 0.15, 0.15 to 0.2, 0.2 to 0.25, 0.25 to 0.3, 0.3 to 0.35, 0.35 to 0.4, 0.4 to 0.45, and 0.45 to 0.5; the mass fraction of the flux can range from 1.6 to 1.7, 1.7 to 1.8, 1.8 to 1.9, 1.9 to 2.0, 2.0 to 2.1, 2.1 to 2.2, and 2.2 to 2.3.
[0027] As an embodiment of the present invention, the mass fraction ratio of the first flux to the second flux is 1.5-1.8:0.1-0.5. The mass fraction of the first flux can range from 1.5-1.6, 1.6-1.7, 1.7-1.8; the mass fraction of the second flux can range from 0.1-0.2, 0.2-0.3, 0.3-0.4, 0.4-0.5.
[0028] As an embodiment of the present invention, the sintering temperature is 300-550°C. The temperature range may be 300-350°C, 350-400°C, 400-450°C, 450-500°C, 500-550°C.
[0029] As an embodiment of the present invention, the sintering time is 1 to 6 hours. The sintering time range can be 1 to 2 hours, 2 to 3 hours, 3 to 4 hours, 4 to 5 hours, or 5 to 6 hours.
[0030] As an embodiment of the present invention, the heating rate of the sintering is 1-5°C / min. The heating rate range may be 1-2°C / min, 2-3°C / min, 3-4°C / min, 4-5°C / min.
[0031] The pretreatment is sintering in a CO2 atmosphere so that the sodium hydroxide on the surface of the positive electrode material powder is converted into sodium carbonate, making the measurement more accurate.
[0032] The sintering furnace used for sintering includes, but is not limited to, a muffle furnace, a tube furnace and an infrared furnace.
[0033] Compared with the prior art, the present invention has at least one of the following beneficial effects:
[0034] (1) The present invention tests the residual alkali content of the positive electrode material of the sodium ion battery by an improved carbon-sulfur method. Preferably, a CO2 pretreatment method is used in the process. This method solves a series of problems in measuring the positive electrode material of the sodium ion battery by the traditional titration method.
[0035] (2) The present invention uses an improved carbon-sulfur method to test the sodium hydroxide content in the residual alkali on the surface of the positive electrode material of the sodium ion battery. A CO2 pretreatment method is used in the process. This method solves a series of problems in measuring the positive electrode material of the sodium ion battery by the traditional titration method.
[0036] (3) Compared with the titration method, the method of the present invention is simple to operate, has high data reliability and good repeatability. DETAILED DESCRIPTION
[0037] The present invention is described in detail below in conjunction with specific embodiments. The following examples are implemented under the premise of the technical solution of the present invention, and provide detailed implementation methods and specific operation processes, which will help those skilled in the art to further understand the present invention. It should be pointed out that the protection scope of the present invention is not limited to the following embodiments, and several adjustments and improvements made under the premise of the concept of the present invention all belong to the protection scope of the present invention.
[0038] The comparison method of the present invention is the traditional residual alkali test method in the field of sodium ion battery positive electrode materials - acid-base titration method, and the specific operation of the acid-base titration method is:
[0039] 1) The test method for residual alkali (sodium carbonate) content in the sample is:
[0040] Weigh the sample in a beaker, record the sample mass y1 grams, add V1 milliliters of ethylene glycol with a pipette, seal the cup mouth with plastic wrap and stir for more than 10 minutes, filter with a funnel after stirring, take V2 milliliters of the filtrate and stir and mix with 2 to 6 times V2 milliliters of pure water to obtain a mixed solution. Add 2 to 4 drops of methyl red-bromocresol green indicator solution to the mixed solution. Then titrate with a standard hydrochloric acid solution with a concentration of c mol / L until the solution changes from green to slightly pink, and record the consumption of hydrochloric acid at this time V3. Calculate the residual alkali (sodium carbonate) content of the sample according to the following formula:
[0041]
[0042] 2) The test method for the residual alkali (sodium hydroxide) content of the sample is:
[0043] Weigh the sample in a beaker, record the sample mass y2 grams, add V4 milliliters of ethanol with a pipette, seal the cup mouth with plastic wrap and stir for more than 10 minutes, filter with a funnel after stirring, take V2 milliliters of the filtrate and stir and mix with 2 to 6V2 milliliters of pure water to obtain a mixed solution. Add 2 to 4 drops of methyl red-bromocresol green indicator solution to the mixed solution. Then titrate with a standard hydrochloric acid solution with a concentration of c mol / L until the solution changes from green to slightly pink, and record the consumption of hydrochloric acid at this time V5. Calculate the residual alkali (sodium hydroxide) content of the sample according to the following formula:
[0044]
[0045] 3) Calculate the total residual alkali content of the sample according to the test results of steps 1) and 2) of the above method, the formula is as follows:
[0046]
[0047] Preparation of standard samples
[0048] The standard sample used in the present invention includes a sodium carbonate standard sample, and the preparation method of the standard sample is as follows:
[0049] The sodium carbonate standard is a mixed powder of sodium carbonate & nano-oxide. The preparation principle of the sodium carbonate standard is: the standard is composed of an inert component and an effective C source, wherein the inert component is a nano-oxide, and the effective C source is anhydrous sodium carbonate. The nano-oxide is a pure phase inert oxide that does not undergo a carbon capture reaction at high temperatures, including but not limited to nano titanium dioxide, silicon dioxide, zirconium dioxide, aluminum oxide, etc. Anhydrous sodium carbonate is selected as a reference reagent (purity 99.99%-100.01%). The preparation method of the standard is: design the standard mass m and the Na2CO3 content S1%, accurately weigh the required masses a1 and b1 of anhydrous sodium carbonate and nano-oxide, where a1 and b1 are calculated as follows:
[0050] a1=m*S1%,b1=m-a1
[0051] The weighed anhydrous sodium carbonate and nano oxide are mixed in the solid phase, and after being mixed evenly, the mixed powder is placed in an oven for drying. There is no specific limitation on the mixing method, as long as the two powders are fully mixed, such as stirring with a planetary mixer, grinding in an agate mortar, high-speed ball milling, etc. The drying conditions are 80°C to 160°C for 2h to 12h.
[0052] The present invention adopts the infrared carbon-sulfur analyzer model CS3500 of Gangyan Nake Testing Technology Co., Ltd. to analyze the carbon content.
[0053] Example 1
[0054] This embodiment provides a method for detecting residual alkali (sodium carbonate) on the surface of a positive electrode material of a sodium ion battery, comprising the following steps:
[0055] 1) The positive electrode material standard samples 1-8 were prepared according to the preparation method of the sodium carbonate standard sample (the contents of sodium carbonate and titanium dioxide are shown in Table 2);
[0056] 2) Weigh 0.25g iron powder and 0.05g B2O3 powder into a crucible dedicated for carbon-sulfur analysis, add 0.08g positive electrode material powder to the crucible, and then weigh 1.6g metal tungsten powder. Input the weight of the powder to be tested and the flux into the instrument software, then place the crucible at the instrument injection port and start the test. After the test is completed, record the measured carbon content of the powder to be tested x1, and calculate the total residual alkali content of the positive electrode material powder to be tested according to the following formula:
[0057]
[0058] Among them, M C is the molar mass of carbon, is the molar mass of sodium carbonate.
[0059] The example data of different test methods for determining sodium carbonate standard samples are as follows: (the titration test step is titration step 1)
[0060] Table 1
[0061]
[0062] The example data for preparing sodium carbonate standard are as follows:
[0063] Table 2
[0064]
[0065]
[0066] Example 2
[0067] According to the steps of Example 1, the repeatability comparison data of the carbon-sulfur method and the titration method are shown in Table 3 below:
[0068] Table 3
[0069]
[0070] Example 3
[0071] This embodiment provides a method for detecting residual alkali (sodium carbonate, sodium hydroxide) on the surface of a positive electrode material of a sodium ion battery:
[0072] 1) According to the preparation method of the above-mentioned standard samples, positive electrode materials were prepared respectively (standard samples 9-11, the contents of sodium carbonate, sodium hydroxide and titanium dioxide are shown in Table 4), 0.3 g of the positive electrode material powder to be tested was weighed in a crucible, the crucible was placed in a muffle furnace, CO2 gas was introduced, and the temperature was raised to 400°C for 4h, and the heating rate was 3°C / min;
[0073] 2) Weigh 0.3g of different second fluxes (including iron powder, copper powder, tin powder, as shown in Table 4) and 0.15g of B2O3 powder into a special crucible for carbon-sulfur analysis, add 0.2g of pretreated positive electrode material powder to the crucible, and then weigh 1.6g of metal tungsten powder. Enter the weighed mass of the powder and flux to be tested into the instrument software, then place the crucible at the instrument injection port and start the test. After the test is completed, record the measured carbon content of the powder to be tested x1, and calculate the total residual alkali content of the positive electrode material powder to be tested according to the following formula:
[0074]
[0075] Among them, M C is the molar mass of carbon, is the molar mass of sodium carbonate.
[0076] The example data of different test methods for measuring sodium hydroxide standard samples are shown in Table 4 below:
[0077] Table 4
[0078]
[0079] Example 4
[0080] This embodiment provides a method for detecting residual alkali (sodium carbonate, sodium hydroxide) on the surface of a positive electrode material of a sodium ion battery:
[0081] 1) Weigh three portions of 0.3 g of the cathode material powder to be tested (sample 1, sodium nickel iron manganese oxide), place them in a crucible, place the crucible in a muffle furnace, introduce CO2 gas, and heat to 400°C for 4 h at a heating rate of 3°C / min;
[0082] 2) Weigh 0.3g iron powder and 0.15g B2O3 powder into a crucible dedicated for carbon-sulfur analysis, add 0.2g pretreated positive electrode material powder into the crucible, and then weigh 1.6g metal tungsten powder. Input the weight of the powder to be tested and the flux into the instrument software, then place the crucible at the instrument injection port and start the test. After the test is completed, record the measured carbon content of the powder to be tested x1, and calculate the total residual alkali content of the positive electrode material powder to be tested according to the following formula:
[0083]
[0084] Among them, M C is the molar mass of carbon, is the molar mass of sodium carbonate.
[0085] 3) Measure the residual alkali of the untreated positive electrode material powder according to step 2)
[0086] 4) From the total residual alkali content ω 总 and The content of sodium hydroxide in the sample to be tested is calculated according to the following formula:
[0087]
[0088] Example 5
[0089] This embodiment provides a method for detecting residual alkali (sodium carbonate, sodium hydroxide) on the surface of a positive electrode material for a sodium ion battery, which is basically the same as the steps in Example 4. The amounts of the pretreated positive electrode material powder to be tested (sample 2 to be tested, sodium nickel manganate), iron powder, B2O3 powder, and metal tungsten powder are shown in Table 6.
[0090] Example 6
[0091] This embodiment provides a method for detecting residual alkali (sodium carbonate, sodium hydroxide) on the surface of a positive electrode material for a sodium ion battery, which is basically the same as the steps in Example 4. The amounts of the pretreated positive electrode material powder to be tested (sample 3 to be tested, sodium copper iron manganese oxide), iron powder, B2O3 powder, and metal tungsten powder are shown in Table 6.
[0092] The example data of different test methods for measuring sodium hydroxide standard samples are shown in Table 5 below:
[0093] Table 5
[0094]
[0095]
[0096] Comparative Example 1
[0097] This comparative example provides a method for detecting residual alkali (sodium carbonate, sodium hydroxide) on the surface of a positive electrode material for a sodium ion battery, which is basically the same as Example 4, except that the iron powder is replaced with an equal amount of metal tungsten powder, as shown in Table 6.
[0098] Comparative Example 2
[0099] This comparative example provides a method for detecting residual alkali (sodium carbonate, sodium hydroxide) on the surface of a positive electrode material for a sodium ion battery, which is basically the same as Example 4, except that the B2O3 powder is replaced with an equal amount of metal tungsten powder, as shown in Table 6.
[0100] Comparative Example 3
[0101] This comparative example provides a method for detecting residual alkali (sodium carbonate, sodium hydroxide) on the surface of a positive electrode material for a sodium ion battery, which is basically the same as Example 4, except that the B2O3 powder is replaced with an equal amount of Al2O3 powder, as shown in Table 6.
[0102] Table 6
[0103]
[0104]
[0105] The example data of the residual alkali standard sample determined by different test methods are shown in Table 7 below: (The titration test steps are titration steps 1-3)
[0106] Table 7
[0107] Standard Carbon-sulfur method test value / ppm Example 4 (sample 1 to be tested) 5009 Comparative Example 1 (Sample 1 to be tested) 4601 Comparative Example 2 (Sample 1 to be tested) 4510 Comparative Example 3 (Sample 1 to be tested) 4658
[0108] Comparative Example 4
[0109] This comparative example provides a method for detecting residual alkali (sodium carbonate, sodium hydroxide) on the surface of a positive electrode material for a sodium ion battery, which is basically the same as Example 3, except that the iron powder is replaced with an equal amount of metal tungsten powder, as shown in Table 6.
[0110] Comparative Example 5
[0111] This comparative example provides a method for detecting residual alkali (sodium carbonate, sodium hydroxide) on the surface of a positive electrode material for a sodium ion battery, which is basically the same as Example 3, except that the B2O3 powder is replaced with an equal amount of metal tungsten powder, as shown in Table 6.
[0112] Comparative Example 6
[0113] This comparative example provides a method for detecting residual alkali (sodium carbonate, sodium hydroxide) on the surface of a positive electrode material for a sodium ion battery, which is basically the same as Example 3, except that the B2O3 powder is replaced with an equal amount of Al2O3 powder, as shown in Table 6.
[0114] The example data of the residual alkali standard sample determined by different test methods are shown in Table 8 below:
[0115] Table 8
[0116] Standard Theoretical total alkali content / ppm Carbon-sulfur method test value / ppm Example 3 (Standard Sample 9) 5662 5546 Comparative Example 4 (Standard Sample 9) 5662 5103 Comparative Example 5 (Standard Sample 9) 5662 5019 Comparative Example 6 (Standard Sample 9) 5662 5157
[0117] The above describes the specific embodiments of the present invention. It should be understood that the present invention is not limited to the above specific embodiments, and those skilled in the art may make various modifications or variations within the scope of the claims, which do not affect the essence of the present invention.
Claims
1. A method for detecting residual alkali on the surface of a positive electrode material for a sodium ion battery, characterized in that: The steps include: Under the action of acidic additives and flux, the carbon content of the sample to be tested is measured by carbon-sulfur method, and then the residual alkali content in the sample to be tested is calculated; The flux comprises a first flux and a second flux; the first flux is metal tungsten, and the second flux is one or more of iron, copper, and tin.
2. The detection method according to claim 1, characterized in that: The sample to be tested is sodium ion battery positive electrode material powder.
3. The detection method according to claim 1, characterized in that: The mass ratio of the sample to be tested to the acidic additive and the flux is 0.05-0.3:0.02-0.5:1.6-2.
3.
4. The detection method according to claim 1, characterized in that: The mass ratio of the first flux to the second flux is 1.5-1.8:0.1-0.
5.
5. The detection method according to claim 1, characterized in that: The acidic additive is B2O3 powder.
6. The detection method according to claim 1, characterized in that: The instrument used in the sulfur-carbon method is an infrared carbon-sulfur analyzer, which measures the CO2 concentration in the combustion gas by infrared absorption and calculates the carbon content in the sample to be tested.
7. The detection method according to claim 1, characterized in that: The residual alkali content is calculated as follows: The carbon content in the sample to be tested is x1, and the total residual alkali content of the sample to be tested is calculated according to the following formula: Among them, M C is the molar mass of carbon, is the molar mass of sodium carbonate.
8. The detection method according to claim 1, characterized in that: The sample to be tested is also pre-treated before testing, and the steps are as follows: the sample to be tested is sintered in a CO2 atmosphere to obtain the pre-treated sample to be tested.
9. The detection method according to claim 8, characterized in that: The sintering temperature is 300-550°C; And / or, the sintering time is 1 to 6 hours.
10. The detection method according to claim 8, characterized in that: The heating rate of the sintering is 1-5°C / min.
Citation Information
Patent Citations
Method for detecting content of residual alkali on surface of sodium ion battery cathode material
CN113092458A
Residual alkali testing method for layered oxide positive electrode material of sodium-ion battery
CN116858989A